Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13018-019-1126-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for upper adjacent segment degeneration after multi-level posterior lumbar spinal fusion surgery

Abstract: Background Posterior lumbar spinal fusion has been widely used in degenerative lumbar stenosis, but adjacent segment degeneration (ASD) was common. Researchers have found many risk factors for ASD after one or two levels of surgery, but few clinical studies focused on multi-level surgery. The purpose of this study was to clarify risk factors for upper ASD after multi-level posterior lumbar spinal fusion. Methods A retrospective study was performed on the clinical data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
2
10
0
2
Order By: Relevance
“…(21,33,34) In our study, P rrmann grade III + severe disc degeneration and presence of disc bulge/protrusion in adjacent segment was signi cantly higher in ASD group. Similar ndings were published by Ma, Ghasemi and Kim et al (13,25,33). More degenerated segments can be more vulnerable for the altered biomechanics resulting in the development of clinically signi cant ASD.…”
Section: Discussionsupporting
confidence: 87%
“…(21,33,34) In our study, P rrmann grade III + severe disc degeneration and presence of disc bulge/protrusion in adjacent segment was signi cantly higher in ASD group. Similar ndings were published by Ma, Ghasemi and Kim et al (13,25,33). More degenerated segments can be more vulnerable for the altered biomechanics resulting in the development of clinically signi cant ASD.…”
Section: Discussionsupporting
confidence: 87%
“…Eight studies (1492 of 2896 patients) [ 14 , 16 , 19 , 20 , 22 , 23 , 29 , 30 ] reported pre- and post-operative SS between ASD group and non-ASD group. There was no significance in the test for heterogeneity and the studies had low heterogeneity (two p for heterogeneity = 0.92, 0.66; I 2 = 0, 0%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although many scholars pay more attention to ASD after spine surgery, the risk factors associated with ASD are controversial. Thus, we perform a meta-analysis to evaluate the risk factors associated with ASD [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The rate of ASD after posterior lumbar fusion surgery was 18.6% (ranged from 8.5 to 69.4%) in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal fusion surgeries are performed in cases of traumatic instability, or when decompression surgery at multiple levels creates this instability. The pathological manifestations of ASD can include degeneration, listhesis, instability, herniation, and osteophyte formation [ 15 17 ]. The etiologies of ASD involve complex biomechanical processes and can be categorized as leading to either increased degeneration or to increased motion in the neighboring segments.…”
Section: Discussionmentioning
confidence: 99%